Parental perception of staff-parent communication in the neonatal unit. (7th June 2011) - Willis, K; Nath, P; Thurlow, C; James, M
Abstract : Background and aim: A high standard of communication between staff and parents in the neonatal unit is a vital part of family centred care. It is essential to the establishment of good working relationships and improves parent-baby bonding. Information provided should be free of medical jargon and presented in a way that parents can easily understand. We aimed to study parents' perception of the quality of communication in the neonatal unit. Method: A 12 point questionnaire was sent by post to the parents of babies admitted to the neonatal unit from August–October 2009. Results: A total of 134 parents were approached and 74(55%) responded. Of the responses 50 (68%) were from mothers and 22 (30%) were from both parents. Gestational age ranged from 28 to 43 weeks (Median 39.5 weeks) and birth weight from 592 to 5020 g (Median 3165 g). 59 (80%) had communication with medical staff within 24 h of admission. 67 (91%) parents were regularly updated during their baby's stay. When asked about the person updating, 40 (60%) were regularly updated by the nurses and 15 (22%) by both nursing and medical staff. 68 (92%) parents were happy with the time spent, ease of understanding and sensitivity of conveyance of the information. 66 (89%) reported overall satisfaction with the communication, 6 (8%) were unsatisfied. Conclusions: The majority of parents were regularly updated and overall were happy with the quality of communication in the neonatal unit. Parents identified nurses as the key source of information.